The Effect of Recruitment, Job Placement and Job Training on the Performance of Employees of the Personnel and Human Resource Development Agency of Lamongan Regency - Laila Rahayu Gianti; Muhamad Imam Syairozi; Abid Muhtarom (Jurnal Multidisiplin Sahombu, 2024)
This study aims to determine the influence of recruitment, job placement and job training on the performance of employees of the Lamongan Regency Personnel and Human Resources Development Agency. The purpose of this study is to find out how the influence of recruitment, job placement and job training on employee performance, whether recruitment, job placement and job training have an influence on employee performance partially simultaneously and which variables are the most dominant affect employee performance. This study uses a quantitative method. The population and sample in this study amounted to 48 people, the data analysis methods used were: validity test, reliability test, multiple linear regression, multiple correlation, determination coefficient, t-test and F test. The results of (1) the t-test (Partial) have been found that the variables of recruitment, job placement, and job training have an effect and significant on the performance of employees of the Lamongan Regency Personnel and Human Resources Development Agency. (2) The results of the F (Simultaneous) test have a simultaneous effect and significance on the performance of the Employees of the Lamongan Regency Personnel and Human Resources Development Agency.